Mechanical recycling and upcycling of marine macro- and micro- plastics: technologies, challenges, and future directions - Ying Teng; Ying Teng; Yitao Zheng; Yitao Zheng; Zheng Wang; Zeping Wang; Zeping Wang; Heng Hu; Hao Zheng; Jianli Duan; Yang Meng; Yang Meng; et al. (Frontiers in Marine Science)
The escalating issue of marine plastic pollution demands urgent and innovative solutions to mitigate its detrimental impacts on ecosystems, human health, and global economies. This paper provides a comprehensive review of mechanical recycling and upcycling technologies for marine macro- and microplastics, addressing the challenges and future directions in their sustainable management. The study systematically examines the processes of collection, cleaning, separation, and melt processing, highlighting advancements and limitations in current methodologies. Recent advancements in marine plastic recycling technologies have addressed the challenges of macroplastic collection and separation, further research into more cost-effective and scalable processes remains imperative for its recycling and upcycling. The recycling of microplastics is much more challenging because of the difficulties in efficient collection and separation. The comprehensive methodologies for the segregation of both macroplastics and microplastics were discussed. The policy framework and technical pathway for marine plastics management was proposed. The paper concludes with actionable recommendations for stakeholders, emphasizing the need for standardized monitoring, improved separation techniques, and global collaboration to combat marine plastic pollution effectively.